Bioactivities, Applications, Safety, and Health Benefits of Bioactive Peptides From Food and By-Products: A Review - Zaky, Ahmed A.; Simal-Gandara, Jesus; Eun, Jong-Bang; Shim, Jae-Han; Abd El-Aty, A. M. (Frontiers in Nutrition, 2022)
Bioactive peptides generated from food proteins have great potential as functional foods and nutraceuticals. Bioactive peptides possess several significant functions, such as antioxidative, anti-inflammatory, anticancer, antimicrobial, immunomodulatory, and antihypertensive effects in the living body. In recent years, numerous reports have been published describing bioactive peptides/hydrolysates produced from various food sources. Herein, we reviewed the bioactive peptides or protein hydrolysates found in the plant, animal, marine, and dairy products, as well as their by-products. This review also emphasizes the health benefits, bioactivities, and utilization of active peptides obtained from the mentioned sources. Their possible application in functional product development, feed, wound healing, pharmaceutical and cosmetic industries, and their use as food additives have all been investigated alongside considerations on their safety. Keywords: Bioactive peptides, Health benefits, Bioactivities, Applications, Safety.